Preparing nurses for palliative and end of life care: A survey of New Zealand nursing schools. (May 2021) - Heath, Lis; Egan, Richard; Ross, Jean; Iosua, Ella; Walker, Robert; MacLeod, Rod
Abstract: Background: Nurses play a vital role in the care of people with advanced life-limiting illnesses, so palliative and end of life care is an essential skill nurses need to learn. Despite numerous reports in the international literature about educational developments in this area, there are widespread inconsistencies in undergraduate education, and graduates continue to report feeling unprepared for this part of their work. Little is known about how New Zealand nursing students learn about this important area of clinical practice. Objectives: To obtain information about teaching content, organisation, delivery, assessment and clinical learning opportunities in palliative and end of life care in undergraduate nurse education in New Zealand. Design: Quantitative descriptive cross sectional study. Settings: Tertiary education institutions that provide the Bachelor of Nursing programme in New Zealand. Participants: Academic leads and course coordinators. Methods: National online survey. Results: A total of 13/18 (72%) educational institutions completed the survey. All integrate palliative and end of life care in their teaching with an identified coordinator at 12 (92%) institutions. Between 1 and 10 h of formal teaching is provided at 11 (85%) institutions where lectures and tutorials are most comon. Clinical placements with specialist palliative care providers are scarce and limited to senior students as elective placements. Assessment of student learning in palliative and end of life care is carried out at seven (54%) institutions, and formally evaluated at 12 (92%). Lack of teaching time and clinical placements with palliative care providers are barriers to increased learning opportunities in palliative and end of life care. Conclusions: This article provides comprehensive information about palliative and end of life care teaching in undergraduate nurse education in New Zealand. Teaching on this subject is not a mandatory requirement so there are inconsistencies in the teaching provided between educational institutions, and significant barriers to development. Mandatory competencies need to be introduced to ensure graduates have the knowledge, skills and attitudes required to provide optimal care for people near the end of life. Highlights: PEOLC is not a mandatory requirement of the curriculum. PEOLC is taught in all schools that responded, although most only provide 1-10 hours formal PEOLC teaching, and there are significant gaps in content and assessment. Lack of curriculum time and clinical placements with palliative care providers are major barriers to development.